KONFLIK BATIN PEREMPUAN DALAM NOVEL ATAS SINGGASANA Karya Abidah El Khalieqy (Tinjauan Psikologi Sastra) - Agustiningsih, Windi (Program Studi Pendidikan Bahasa dan Sastra Indonesia, 2019)
Agustiningsih, Windi. 2013. Inner Conflict Prominent Women in Novels AtasSinggasana works Abidah El Khalieqy (Psychology Literature Review). Thesis. The purpose of this research is to describe the structure of the novel, the inner conflictexperienced by women leaders, women leaders and solutions to overcome inner conflict.The method used in this research is descriptive qualitative method, which aims todescribe the inner conflict Prominent Women in the Novels Atas Singgasana worksAbidah El Khalieqy (Psychology Literature Review). The results showed that thestructure of the novel, the inner conflict experienced by women leaders, women leadersand solutions to overcome inner conflict found in every sentence, paragraph, or a chapterin the novel Atas Singgasana. The structure of the novel there are 20 data, there are 9inner conflict data, and solutions to resolve inner conflicts are 8 data